2009
DOI: 10.1007/s11832-009-0187-4
|View full text |Cite
|
Sign up to set email alerts
|

Arthrogryposis multiplex congenita. Long-term follow-up from birth until skeletal maturity

Abstract: We conclude that long-term ambulatory status at skeletal maturity is not correlated with the severity of condition at birth. A prognosis for ambulation at skeletal maturity will be done before 2.5 years of age. We believe that early aggressive management of children with severe arthrogryposis is warranted and justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 44 publications
1
70
0
13
Order By: Relevance
“…In a recently published long-term follow-up study [24], all independent or community walkers were reported to have plantigrade feet, despite foot deformities at birth. In children with joint contractures, improved postural alignment of the body segments can be obtained by adding wedges under the heels [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published long-term follow-up study [24], all independent or community walkers were reported to have plantigrade feet, despite foot deformities at birth. In children with joint contractures, improved postural alignment of the body segments can be obtained by adding wedges under the heels [13].…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs formes cliniques d'arthrogrypose ont été décrites. L'amyoplasie ou arthrogrypose multiple congénitale est le type le plus fréquent (un tiers des cas) [8,13]. Sa prévalence est de 1/10 000 naissances vivantes.…”
Section: Discussionunclassified
“…En las extremidades superiores se tienen como hallazgos comunes la disminución o ausencia de pliegues en zonas de flexión, la rotación interna del hombro y la ausencia o limitación marcada de flexión de codo, mientras que en la muñeca se encuentra flexión extrema y desviación cubital (6)(7)(8)(9)(10). A su vez, los dedos adoptan diferentes tipos de deformidades entre las que se encuentran la camptodactilia y aducción del pulgar (3,8).…”
Section: Introductionunclassified
“…Cuando hay compromiso significativo de los miembros superiores, las metas principales son lograr que el paciente consiga realizar sus actividades básicas y una alimentación individual (8,9).…”
Section: Introductionunclassified